Evaluasi Kualitas Pelayanan Kesehatan Dasar Terhadap Kepuasan Pasien Di Puskesmas Kota Bukittinggi Tahun 2019 - Sri Yus Angelia (Jurnal Visi Manajemen, 2019)
This research was motivated by the results of the BPJS assessment of the Guguk Panjang Health Center where the impression value of the Guguk Panjang Health Center was 66.25%. The research method used is a quantitative approach. Data collection technique used is the distribution of questionnaires. Data analysis uses Outer Loading and Inner Loading Analysis, while data processing is assisted by using SemPLS software. Based on the research results, the authors conclude that the quality of basic health services is related to patient satisfaction. There is a relationship between the dimensions of service quality simultaneously. From the results of the study, it was found that the variable dimension of service quality that has the greatest effect on patient satisfaction is the Assurance (Skills) dimension with an Original Sample value of 0.222, the second is environmental comfort with hypothetical results (p value 0.017), while the smaller dimension is Empathy. (p.Value 0.50%). Whereas for the dimension of Staff Reliability there is no relationship with Patient Satisfaction with a hypothesis value of 0.449 > 0.05 as well as the Responsiveness and provision of information dimension has no relationship with patient satisfaction with a value of 0.535 > 0.04. Thus patient satisfaction with services at the Bukittinggi City Health Center is prioritized for an increase in the dimensions of Reliability and Responsiveness of Officers.